EFFECT OF SUPPLEMENTATION OF CONCENTRATE ON GROWTH PERFORMANCE OF SIROHI GOATS IN THEIR NATIVE TRACT - LAWANIA, PANKAJ (Indian Journal of Animal Production and Management, 2017)
The investigation was carried out on-farm, in the Pabuda village of Sirohi block inSirohi District Rajasthan, located in the native tract of Sirohi Goats. In order to study theeffect of supplementation of concentrates, 30 male kids were randomly divided into threeequal groups and kept either on normal browsing (as per farmer’s practices); (G1) withadditional supplementation of concentrate mixture at 100 (G2) and 150 (G3) g per day perkid. During the experiment period of 120 days, BW of kids was recorded fortnightly. Theaverage daily gain (ADG) of the kids was 31.32+ 0.47, 54.02+0.11 and 62.84+ 0.37 in G1,G2 and G3 respectively with significant differences(P